STRATEGI BRANDING WISATA SYARIAH PULAU MADURA: Teguh Hidayatul Rachmad - Jurnal COMMED (Commed : Jurnal Komunikasi dan Media, 2017)
Madura consists of four districts, namely Bangkalan, Sampang, Pamekasan and Sumenep have the demographics and history of Islamic breath. Islands that are around the island of Madura, eventually also drifted Islamisation. Some of the historical heritage of Islamic nuanced evidence of cultural artifacts until now. The mosque, the burial place, the kingdom, to the place that made religious rituals in ancient times is still maintained until now. The method used is a qualitative descriptive categorize and describe various data literature has been obtained. The result is a cultural artifact of the Madurese be an attraction that is used as a tourist destination branding that based on sharia. Many Islamic cultural artifacts so Madura considered a portico Medina. Portico Medina branding process must be maintained and widely publicized, so that people inside and outside Indonesia aware of the beauty and culture of Madura.